2020
DOI: 10.48550/arxiv.2008.04621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

R-MNet: A Perceptual Adversarial Network for Image Inpainting

Abstract: Facial image inpainting is a problem that is widely studied, and in recent years the introduction of Generative Adversarial Networks, has led to improvements in the field. Unfortunately some issues persists, in particular when blending the missing pixels with the visible ones. We address the problem by proposing a Wasserstein GAN combined with a new reverse mask operator, namely Reverse Masking Network (R-MNet), a perceptual adversarial network for image inpainting. The reverse mask operator transfers the reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…GAN models for image inpainting [20,33,34] have used multicolumns to encode and propagated features directly to the decoder or use a selfsupervised Siamese style inference approach [21], where a style encoder is the supervisor of the generator, to improve feature extraction and learning. Other methods [35,25,18] observed that failures in feature extraction and propagation could be due to the irregular holes. To address the limitation, Liu et al [11] proposed an independent mask updating with partial convolutions to specifically target missing regions.…”
Section: Learning-based Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…GAN models for image inpainting [20,33,34] have used multicolumns to encode and propagated features directly to the decoder or use a selfsupervised Siamese style inference approach [21], where a style encoder is the supervisor of the generator, to improve feature extraction and learning. Other methods [35,25,18] observed that failures in feature extraction and propagation could be due to the irregular holes. To address the limitation, Liu et al [11] proposed an independent mask updating with partial convolutions to specifically target missing regions.…”
Section: Learning-based Methodsmentioning
confidence: 99%
“…Yu et al [25] proposed to use gated convolutions to gear the model towards learning soft mask of the irregular hole regions. More recently, Jam et al [18] proposed a reverse mask mechanism to specifically target missing regions whilst preserving the visible ones using a spatial preserving operation.…”
Section: Learning-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations